THE ROLE OF LOCAL TV STATIONS IN SOUTH SULAWESI IN IMPROVING THE QUALITY OF JUNIOR HIGH SCHOOL (SMP) EDUCATION MANAGEMENT - Mansyur, Muhammad; Anas, Afdal; Nurramadhani, Rezki; Adnan, A.Evi Elvira (Entrepreneurship Undergraduate Program at Amkop Business School, 2024)
This study examines the role of local television stations in South Sulawesi in supporting education management at the junior high school (SMP) level. Through qualitative methods, this research involves interviews with television program managers, school principals, teachers, parents of students, and officials of the Education Office. The findings of the study show that local TV stations help improve the quality of education management by disseminating important information, providing alternative learning programs, and facilitating community participation in school activities. Local TV stations also face several challenges, such as limited broadcast coverage, budget limitations, and content quality that still needs to be improved. The conclusion of this study emphasizes the importance of support from the government and the community to maximize the role of local TV stations in improving the quality of education in South Sulawesi.Keywords: Local TV stations, junior high school education, education management, South Sulawesi.